Incorporating Remote Electrical Neuromodulation (REN) Into Usual Care Reduces Acute Migraine Medication Use: An Open-Label Extension Study - Marmura, Michael J.; Lin, Tamar; Harris, Dagan; Ironi, Alon; Rosen, Noah L. (Frontiers in Neurology, 2020)
Background A recent randomized controlled study showed that 66.7% (66/99) and 37.4% (37/99) of people undergoing remote electrical neuromodulation (REN), a novel non-pharmacological migraine treatment, achieve pain relief and pain freedom, respectively, at 2 hours post-treatment. Participants who completed the 6-weeks double-blind phase of this study were offered to participate in an open-label extension (OLE) with an active REN device. Objective This study investigated the clinical use of REN, focusing on its potential in reducing the use of acute migraine medications. Methods The parent study for this open label extension (OLE) was a randomized, double-blind, sham-controlled study of acute treatment conducted on 296 participants enrolled at 12 sites in the USA and Israel. This study included a run-in phase, in which migraine attacks were treated with usual care, and an 8-week double-blind treatment phase. One hundred and sixty participants continued in an 8-week OLE phase in which they could incorporate a REN device into their usual care. Medication use rate (percentage of participants who treated their attacks only with REN and avoided medications in all their attacks) and pain outcomes at 2 hours post-treatment were compared between the OLE and the run-in phase in a within-subject design. Results The analyses were performed on 117 participants with episodic migraine. During the OLE, 89.7% of the participants treated their attacks only with REN and avoided medications in all their attacks compared with 15.4% in the run-in phase (p<0.0001). The rates of pain relief and pain-free in at least 50% of the treatments at 2 hours post-treatment were comparable (pain relief: 58.1% in the run-in phase and 57.3% in the OLE, p=0.999; pain-free: 23.1% in the run-in vs. 30.8% in the OLE, p=0.175). Conclusions REN may reduce the use of acute migraine medications. Thus, incorporating REN into usual care may reduce the risk for medication overuse headache (MOH). Future studies should evaluate whether REN reduces the use of acute migraine medications in a population at risk for MOH.